La doctrina de la profanación (2017)
"The childish image is a graphic construction that aims to convey a message to infants so that they have a better approach to reality, allowing them to grow and learn in the best way possible. However, becoming an adult does not completely lose that inner child, who is provided with creativity, eagerness to play and some innocence. From this exploration, a search was made to address a language of juxtaposition, which contrasts a caricatured medium of childish drawing with a crude representation of reality, provided with negative issues for society such as violence and grotesque. In this way the concept of the adult who has everything under control is criticized, as opposed to the child who is incapable of possessing knowledge." -- Tomado del Formato de Documento de Grado.